“UTILIZING TERRAIN FEATURES FOR FUNCTIONAL AND RECREATIONAL ENHANCEMENT IN URBAN LANDSCAPE DESIGN” - Eshmamatov Xushnudbek Obidjonovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article examines methods of integrating terrain features, water bodies, and vegetation in urban landscape design to enhance ecological, aesthetic, and recreational value. It explores how natural slopes, hills, valleys, and artificial elevationscan shape urban spaces, support microclimate regulation, and improve biodiversity. The study analyzes international approaches from Europe and North America alongside local practices in Central Asia, highlighting innovative strategies for functional zoning, recreational development, and ecological sustainability. Findings emphasize the importance of harmonizing terrain, water, and vegetation to create urban environments that are visually appealing, socially engaging, and environmentally resilient